A review on Alumina based ceramic composites as cutting and machining tool materials - Mary, Donnabelle Balela; V., Vannaladsaysy; Zuhailawati, Hussain (Universiti Malaysia Perlis, 2010)
Link to publisher's homepage at http://jere.unimap.edu.my